PENGARUH BAURAN PEMASARAN TERHADAP PENDAPATAN USAHATANI KOPI DI DESA KOPIDIL KECAMATAN KABOLA - Emirensiana Latuan; Ferdinan Demang (Politeknik Pertanian Negeri Kupang, 2023)
To determine the simultaneous significant effect of product, price, location and promotion on increasing coffee farming income in Kopidil Village, Kabola District. Kabola. The sample in this study was a saturated sample technique so that all populations were sampled, namely 55 people. The analytical method uses the t test and F test. The data obtained is analyzed by several stages of analysis, namely the F test and t test. The F test shows that the variables of product, price, promotion), and location (independent variables) in this study have a significant effect on farmers' income. The t-test shows that the variables: product and price have a positive and insignificant effect on farmers' income while the promotion and location variables have a positive and significant effect on farmer's income Keywords: Marketing mix, income, coffee farming